Diketopyrrolopyrrole‐Porphyrin Conjugates with High Two‐Photon Absorption and Singlet Oxygen Generation for Two‐Photon Photodynamic Therapy. (4th November 2014) - Schmitt, Julie; Heitz, Valérie; Sour, Angélique; Bolze, Frédéric; Ftouni, Hussein; Nicoud, Jean‐Francois; Flamigni, Lucia; Ventura, Barbara
Abstract: Two‐photon photodynamic therapy is a promising therapeutic method which requires the development of sensitizers with efficient two‐photon absorption and singlet‐oxygen generation. Reported here are two new diketopyrrolopyrrole‐porphyrin conjugates as robust two‐photon absorbing dyes with high two‐photon absorption cross‐sections within the therapeutic window. Furthermore, for the first time the singlet‐oxygen generation efficiency of diketopyrrolopyrrole‐containing systems is investigated. A preliminary study on cell culture showed efficient two‐photon induced phototoxicity. Abstract : Empfänglich für Anregungen : Die Titelverbindungen zeichnen sich durch große Zweiphotonabsorptionsquerschnitte und die Fähigkeit zur effizienten Erzeugung von Singulett‐Sauerstoff aus. Dadurch sind sie interessant als Sensibilisatoren für die photodynamische Therapie unter Zweiphotonenabsorption (TPA).